Identification of students' science process skills in Basic Physics Practicum II in using e-module - Artha Lumbantoruan; Didik Irawan; Harina Remalis Siregar; Dear Lumbantoruan; Neng Ria Nasih; Sofia Christine Samosir; Utari Prisma Dewi; Dodi Setiawan Putra; Orin Hidayusa Wiza (Jurnal Riset dan Kajian Pendidikan Fisika, 2019)
Good science process skills demonstrated by the attitude of students in conducting experiments in the laboratory. This study aims to determine the mastery of science process skills of students of Physics Education in Universitas Jambi, both students who use the printed Guidebook and students who use the e-module as guide in practicum activities by reviewing eight aspects of integrated science process skills. This study uses a quantitative approach with experimental research methods, namely true experimental. In the study sample used was a student of Physics Education were divided into two groups, 35 students for experiment class and 30 students for control class. Assessment instruments used were observation sheet science process skills with a score of skills used in the form of Likert scale. Based on the analysis score mastery of integrated science process skills of students in the experimental class, operationally defining variables have the highest percentage of 51.4% to the category of very good, whereas in the control class, analyzing aspects of investigations has the highest percentage of 53.3% with a good category.Keywords: college, integrated science process skills, practicum, reflection on a flat mirror